Home in the Poetry of Saudi Arabia Poets: Mohammad ibn 'Abboud Al-'Amoudi an Example of a Distinguished Arab (2) - Yahya Saleh Hasan Dahami (Khazanah Pendidikan Islam, 2023)
The poet communicates the graceful emotions that rise in the hearts of every person toward their homeland because of their love for it. Saudi poets enjoy writing poetry that celebrates the dignity of nationalism. The love of one's homeland, obsession with it, laboring for it, defending and preserving it, and having it run in one's soul are all aspects of nationalism. The researcher aspires to highlight Mohammad ibn 'Abboud Al-'Amoudi's expertise, knowledge, and competence while also highlighting his love for his homeland, the Kingdom of Saudi Arabia, through the poem "Land of Benevolence" as the second part. The researcher tries to present the uses of poetic imagery and symbols in the poem in an effort to assess the talent of the poet. A brief introduction sets the stage for the research, which is then followed by an examination of Saudi poetry analysis and a look at the Saudi poet Mohammad ibn 'Abboud Al-'Amoudi. The critical-analytical-descriptive analysis of the poem "Land of Benevolence" serves as the study's main focus. The study after that uses a critical-analytical approach, with the idea of homeland serving as its focus. It concludes with findings and a conclusion.